TOURISM DEVELOPMENT FOR TAMAN WISATA CANDI BOROBUDUR (TWCB) - Komang Ratih Tunjungsari (Jurnal Hospitality dan Pariwisata, 2020)
ABSTRACT As one of the iconic Buddhist temple and touristic site in Central of Java, Indonesia, Borobudur has developed its status into UNESCO World Heritage since 1991. This means the project for Borobudur’s development become in continuity with the number of tourists visit each day. In one side, the development should not harm the site otherwise, it should be conserved the site and rethinking about carrying capacity of the tourists. The main concept of this paper used for development of Borobodur is as visitor attraction management, four realms of visitor experience that should be counted when developing a visitor attraction, namely entertainment, education, aesthetic and escapism. Literature review mostly used for the methodology of this paper and also explorative description from some sources. The author will develop the temple compounds of Borobudur and the image of the temple compounds will be seen as historical, religious and cultural values that can be enjoyed as the quality tourism toward the international visitors. The objectives of developing the temple compounds’ are not only to pursue the number of the visitors but also to expand the value of sustainable cultural to enhance the visitors’ experience. From the concepts, development should be delivered in the way of marketing, in dealing with the competitors, bringing the sustainable concept toward visitor’s experience and working with the ethics of UNESCO. Keywords : development, stakeholders, visitors attraction management